Self-medication with antibiotics in Georgian population - Darakhvelidze, Marina; Kalandadze, Iagor; Mirzikashvili, Nino; Tsereteli, David; Zakareishvili, Natalia; Ketchakmadze, Ivane (Frontiers in Pharmacology, 2024)
Background: Self-medication with antibiotics is a global phenomenon and a potential contributor to human pathogen resistance to antibiotics. It involves obtaining medication without a prescription, taking medicines based on the advice of friends and relatives, or previous treatment experience. Self-medication is common in both developed and developing countries; however, the prevalence of self-medication is higher in developing countries. The aim of this study was to determine the characteristics of antimicrobial self-medication in Georgia and its potential to influence the overall situation regarding antimicrobial consumption in the country. Methods: We conducted a cross-sectional study using a random sampling method and developed a self-administered questionnaire to collect the data. The survey was conducted via the Internet using the Google Forms platform. Results: The overall number of respondents was 742 adults living in Georgia. The results showed that 23.8% (n=177) of adults had consumed antibiotics without a doctor's prescription, and 12.7% (n=94) confirmed the use of antibiotics by their own decision to treat minor family members. The total prevalence of self-medication was 32.6%. The data analysis revealed a correlation between factor F1 ("personal experience") and gender (p=0.042, F=2.6), and between age and factor F2 ("lack of trust in medical practitioners") (p=0.047, F=2.691). The correlation was stronger among young adults (aged 18-24) and senior adults (aged 60+). The correlation between the level of education and factor F2 was stronger (p=0.00; F1=7.9) than with factor F1 (p=0.04; F=2.2). Conclusion: Self-medication is prevalent in Georgia; pharmacies are the main sources of antimicrobials. No correlation was found between factor F2, pertaining to 'lack of trust in medical practitioners' and gender, between age and factor F1, linked to 'personal experience.' The study uncovered a lack of knowledge about self-medication with antibiotics and emphasized the importance of public awareness campaigns and implementing effective interventions to regulate the sales of antibiotics without a doctor's prescription.